(untitled) (Indonesian Court and Justice Review, 2024)
Judicial review serves as a crucial instrument for constitutional oversight and the protection of fundamental rights. This study provides a comparative analysis of judicial review mechanisms in Indonesia and selected ASEAN countries, including Malaysia, Thailand, and the Philippines. It examines institutional design, procedural access, jurisdictional scope, and the practical impact of constitutional review in each system. Utilizing a comparative legal methodology, the research highlights significant differences in how constitutional courts or supreme courts exercise judicial review across the region. The findings reveal that while Indonesia’s Constitutional Court has a broad and active role, other ASEAN countries show varied degrees of institutional independence and procedural accessibility. The study identifies gaps in Indonesia’s system, such as challenges in enforcement and limited citizen access, while drawing lessons from regional practices that offer more participatory or flexible models. The novelty of this study lies in its regional scope and its effort to bridge comparative constitutional theory with practical institutional performance. By situating Indonesia’s system within the ASEAN legal landscape, the research contributes to discussions on constitutional reform and judicial effectiveness in emerging democracies.